Characterization of silane-based hydrophobic admixtures in concrete using TOF-MS. (April 2015) - Herb, Hartmut; Gerdes, Andreas; Brenner-Weiß, Gerald
Abstract: Silane-based hydrophobic admixtures especially alkyltrialkoxysilanes are used as water repellent agents for the surface protection of concrete. To optimize the structure of alkyltrialkoxysilanes in terms of their performance and their long term durability it is important to understand the chemical reactions taking place between the silicon organic compounds and the materials on which they are applied. For this purpose the characterization of alkyltrialkoxysilanes and their reaction products in concrete is necessary. Therefore we adapted an analytical method based on time-of-flight mass spectrometry (TOF/MS) combined with electrospray ionization (ESI) and matrix assisted laser desorption ionization (MALDI). Monomeric alkyltrialkoxysilanes could be analyzed by the former method, reaction products which could be identified as Silsesquioxanes (SSOs) by the latter one. The results indicate that ESI-TOF/MS and MALDI-TOF/MS serve as a reliable and convenient tool to characterize monomeric silane-based hydrophobic admixtures as well as their reaction products resulted from hydrolysis and condensation.